Tinjauan literatur sistematis pemanfaatan electronic document management system bagi organisasi dalam menunjang manajemen pengetahuan - Ansori Anas; Tamara Adriani Salim (Perpustakaan Universitas Gadjah Mada, 2022)
Introduction. Organizations need information systems to facilitate document management in support of their business processes that can be managed through EMDS. This study aims to find out the literature on the benefits of EDMS in supporting knowledge management. Data Collection Methods. This study uses the Systematic Literature Review (SLR) method on the results of journal articles regarding the use of EDMS in supporting knowledge management during 2015-2020. The stages of SLR research use three stages, namely planning, collecting and reporting. Data Analysis. Research data using descriptive analysis presented with simple statistical tables.. Results and Discussion. There are ten articles showing that EDMS used in various organizations can assist in the management of KM information assets such as storage, distribution, security that can improve organizational performance that needs to be supported by good human resources. Conclusion. HR plays an important role in information management through the use of EDMS to support KM. This research provides awareness of the importance of utilizing EDMS and competent human resources in KM management in organizations. The collection of articles uses two databases so that the data obtained is still limited.